School Violence Through Digital Means: From Bullying to Cyberbulliyng - Gassó, Aina M.; Fernández-Cruz, Victòria; Montiel, Irene; Agustina, José R. (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
Since approximately forty years ago, traditional bullying has been consolidated as one of the most affecting issues for adolescents worldwide. Since then, a great number of researches have been published on the topic, in order to fully understand this phenomenon, and establish effective intervention and prevention programmes. However, over the past few years with the rapid development of the new technologies, the cyberbullying has emerged as a new phenomenon, directly derived from bullying. This paper aims to review the current information on this relatively new issue in order to understand the implications of the technological dimension of bullying.
Keywords: bullying; cyberbullying; adolescents; school violence; technology; online victimisation